Citizens’ legislative initiative in practice: on the debate concerning the project “Stop Abortion” (Economic and Political Thought, 2019)
The work focuses on the analysis of the 2015 citizens’ legislative initiative“Stop Abortion” and gives a careful thought to this instrument in the lightof the assumptions of the theory of liberal democracy. I reconstruct the circumstancesof the legislative initiative, its political, social and cultural contextand the discussion on the project in the Sejm. A citizens’ legislative initiative(CLI) as a new democratic instrument was intended to be a response to problemsand deficiencies of democracy in Poland, an idea to make social andpolitical life democratic by increasing general activeness of citizens and theirparticipation in taking state decisions.I analyse the CLI of “Stop Abortion” as a project activating a broad,individual and organised, citizens’ initiative in the “world of life” and if itmeets the requirements of participative democracy. Political actors treat thisbig social and cultural capital gathered around the initiative “Stop Abortion”in an instrumental way.The discussion on the “Stop Abortion” project in the Sejm is a denial ofthe requirements of deliberative democracy. Simply speaking, the initiatorsof “Stop Abortion” impose their subjective point of view on the state, whichthey want to use as a tool in popularising their views as legally binding rules,which is in conflict with values and endangers the foundations of liberaldemocracy. It is also an indication of degradation of public language andpolitical communication.
Keywords: citizens’ legislative initiative, legislative initiative, debate, abortion